Local Wisdom Values as Social Attachment of School and Multicultural Society (the Implementation of Multicultural Education at Muhammadiyah Islamic School Sendangmulyo, Kulon Progo, Yogyakarta) - Sumarni, Sri (International Journal of Engineering and Technology, 2018)
Through peace, the world civilization will be implemented. Meanwhile, peace will be created if each nation in the world is able to build tolerance and cooperation in multicultural society context. Indonesia has owned a motto â€œBhinneka Tunggal Ikaâ€ which becomes the base of nation unification, while in the local areas, the local wisdom values which become the various societies. In Yogyakarta in particular, or Javanese in Geneal, many local wisdom values that can become social attachment in multicultural societies. This research is aimed to explain the form of interaction and local wisdom values which are able to strenghten the relationship of a school with the multicultural societies. Through qualitative-naturalistic method, this research is performed to draw a conclusion that the relationship basic in the interaction between the school and society is trust. Trust is built from social values sourced from local wisdoms, which is â€œcooperationâ€ full of sincerity or which is called as â€œholobis kuntul baris.â€ This value has given societys spirit since the building of this school. Eventhough the society and school have difference religions, they let their children to study at thi school. Also, theres no anxiousness towards their childrens learning activity. Until nowadays, the school and society have been able to maintain the local wisdom values even to keep and protect each other. They have belief that â€œeventgough they have different religions, they have similar ancestor so that they should not hurt each other, even they have to respect and help each other.â€ In the concept of multicultural religious education, it has entered the level of â€œbeyond the wallâ€. According to Christina and Intersubjective step according to Abdullah. It is the implementation of Multicultural Education which is based on local wisdom which is continously dug in many regions in Indonesia.Â